Under the Publisher's Undifferentiated Patronage: A Corpus-Based Case Study of Chinese Editorial Censorship on Translation about EU-Russia Relationship. - Jianwei, Zheng (Critical Arts: A South-North Journal of Cultural & Media Studies, 2025)
This article sets out to study how a publisher's in-house editor in China censors the faithfully translated evaluation of the political stance of Russia and the European Union ("EU") in a translated book on EU-Russia relationship based on a tagged corpus of the editor's manuscript. The study finds that the editor tends to positively revise, via modification or deletion, evaluations of Russia's stance and negatively of the EU's stance. Specifically, the editor mostly understates the negativity of critical content about Russia's domestic and bilateral stance to typically shift the author's description of Russia as an authoritarian or aggressor, while overstating the negativity of the EU's bilateral stance to augment its austerity towards Russia. Adulterating the faithful translation, the editorial censorship is supported by the undifferentiated patronage of the publisher as the project funder and the authorized censor in China where compulsory ideological censorship works covertly and effectively in the publishing industry.